Ion beam modification of biological materials in nanoscale - Yu L.D. (2014)
Ion interaction with biological objects in nanoscale is a novel research area stemming from applications of low-energy ion beams in biotechnology and biomedicine. Although the ion beam applications in biotechnology and biomedicine have achieved great successes, many mechanisms remain unclear and many new applications are to be explored. We have carried out some research on exploring the mechanisms and new applications besides attaining ion beam induction of mutation breeding and gene transformation. In the studies on the mechanisms, we focused our investigations on the direct interaction in nanoscale between ions and biological living materials. Our research topics have included the low-energy ion range in DNA, low-energy ion or neutral beam bombardment effect on DNA topological form change and mutation, low-energy ion or neutral beam bombardment effect on the cell envelope and gene transformation, and molecular dynamics simulation of ultra-low-energy ion irradiation of DNA. In the exploration of new applications, we have started experiments on ion irradiation or bombardment, in the nanoscaled depth or area, of human cells for biomedical research. This paper introduces our experiments and reports interesting results. © 2011.